MECHANISMS OF PSYCHO-PHYSIOLOGICAL METHODS OF REGULATION OF FUNCTIONAL STATES AMONG POLICE OFFICERS - Kodlubovskaya, Tetiana (PSYCHOLOGICAL JOURNAL, 2018)
The article examines the results of the study of the effect of a complex of individually selected breathing techniques in conjunction with phytoarhomics and acupressure and mechanisms of their impact on the psychophysiological indicators of the functional conditions of police officers. In the group where the studies were carried out with the individual form of the classes, the number of people with signs of emotional tension, aggressiveness and anxiety decreased reliably. The indicators of the states increased: well-being, activity and mood. Confidence of the improvement in their indices of the reserves of the cardiovascular system and the adaptive potential was confirmed. The results of the study convincingly state that the potential capabilities of individually-matched respiratory techniques in combination with phytoharmaceuticals and acupressure in a short time (up to 10 minutes) allow normalizing psychophysiological potential and vegetative balance among police officers. The obtained data testify to the important role of the training of police officers in the field of psychophysiological self-regulation of functional states after stress for their normalization and prevention of posttraumatic and psychosomatic disorders. The complex method of psychophysiological regulation (CMPR) of the functional states of police officers set forth in the article is based on the psychophysiological mechanisms of the individual personality approach (IPA), psychological and biological feedback (BOS). The technique of this method consists of the stages: express diagnosis (self-diagnosis), express - analysis (self-analysis) of information received about psycho-physiological indicators of functional states, individual selection of methods of regulation, performance of techniques regulation (self-regulation) and control diagnostics of psychophysiological indicators after applying a complex method of regulation. The results of the use of CMPR are statistically reliable. The method has a number of patents and is confirmed by acts of implementation. Key words: antistress respiratory fitoaroma regulation, acupressure, individual-personal approach, psychological and biological feedback, independent psychophysiological normalization of functional states.